Informalitas Dalam Formalitas: Sebuah Kajian Budaya Organisasi Perusahaan Keluarga - Hardiyanti Munsi; Ahmad Ismail (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2018)
This article intends to identify and to describe the unique structure and the managing style that owns primordial characteristics, that is giving significance to kinship, religion, and local Bugis cultural values, which made up the cultural system of PT. Hadji Kalla family business. Theoritically, this research was inspired from Weberian perspective on the ideal types of bureaucracy, that observes organizations (in this case is the family business) as one of the socio-cultural phenomena which is neutral and value-free, that is place aside its subjective aspects. The research was conducted in two locations, the head office and one of the branch offices using qualitative approach that relies on participant observation, in-depth interviews, and literature studies. The results of the research shows that the family business of PT. Hadji Kalla that has advanced into national level still prioritizes kinship, ethnicity, and religious aspects in the daily activities of the company. The value even take parts in providing the company’s colour to the urban societies in various districts where the company stands. This means that although the society has undergone transformations, it doesn’t mean that the primordial value, and the elements that exist outside of businesses (such as kinship, big men, religion, cultural values, and interest) do not influence the activities that are held in formal organizations. Therefore, the interventions of subjective aspects will always appear, followed with the application of the modern management system that is implemented by PT. Hadji Kalla company.